Energies of the first excited 2+ states in 122Sn and 122Te - A. P. Lashko; T. N. Lashko (Ядерна фізика та енергетика)
High-precision energy measurements of the most intense γ-transitions from the decay of 122Sb (Т1/2 = 2.72 days) have been performed with a γ-spectrometer. Using this data, the energies of the first excited states and corresponding deexciting γ-rays in 122Sn and 122Te were determined with precision up to a few electron volts.